Bioactive Variability and In Vitro and In Vivo Antioxidant Activity of Unprocessed and Processed Flour of Nine Cultivars of Australian lupin Species: A Comprehensive Substantiation - Kishor Mazumder; Afia Nabila; Asma Aktar; Asgar Farahnaky (MDPI AG, 2020)
The aim of this present investigation was to analyze bioactive compounds, as well as demonstrate the antioxidant activities of nine cultivars of Australian lupin species accompanied by observing the effect of domestic heat processing on their antioxidant activities adopting in vivo and in vitro approaches. Gas chromatography mass spectroscopy (GC-MS) analysis was performed for profiling bioactive compounds present in lupin cultivars. Multiple assay techniques involving quantification of polyphenolics, flavonoids and flavonol, electron transfer (ET) based assay, hydrogen atom transfer (HAT)-based assay and in vivo assays were performed. The major compounds found were hexadecanoic acid methyl ester, 9,12-octadecadienoic acid methyl ester, methyl stearate, lupanine,13-docosenamide and 11-octadecenoic acid (Z)- methyl ester. Mandelup was found to show excellent antioxidant activity. Moreover, Jurien, Gunyidi and Barlock had strong antioxidant activity. Both positive and negative impacts of heat processing were observed on antioxidant activity. Heating and usage of excess water during processing were the key determinants of loss of antioxidants. Negligible loss of antioxidant activity was observed in most of the assays whereas inhibition of both lipid peroxidation (33.53%) and hemolysis of erythrocytes (37.75%) were increased after processing. In addition, in vitro and in vivo antioxidant assays are found to show statistically significant (* p < 0.05 and ** p < 0.01) results, which are supported by the presence of a number of antioxidant compounds in GC-MS analysis.